Determinación microbiológica y de metales pesados en toronjil (Melissa officinalis) y taraxaco (Taraxacum officinale), expendidos en los diferentes mercados del distrito metropolitano de Quito. - Carrera Núñez, Ángel Alexander (2016)
Melissa and taraxaco are widely consumed in the Metropolitan District of Quito as medicines and food, in this work was evaluated, the condition of melissa and taraxaco expended in 30 markets of the DMQ, through the collection of composite samples which were subjected to morphological characterization, determination of: pH, ashes, humidity, lead and cadmium, also microbiological and parasitological analysis; the results were analyzed using ANOVA (P <0.05). Significant differences were found between markets, it was identified that markets: Las Cuadras, Comité del Pueblo, La Kennedy, and Santa Clara exceed the permissible limits of total aerobes in melissa and taraxaco. All markets are above permissible limits. Parasitological analysis came back positive in 80% of markets that expend melissa and 68% in markets that expend taraxaco.